Elastic interaction energy of point defects with a basal dislocation loop in zirconium - Trotsenko, O.G.; Babich, A.V. (Вопросы атомной науки и техники, 2020)
Based on the tensor Green's function for hexagonal crystals obtained by the Lifshitz-Rosenzweig method, the analytical expression of the elastic interaction energy of radiation point defects is calculated in the model of force dipoles with a dislocation vacancy loop (basal plane of occurrence {0001}, Burgers vector bᴰˢ = 1/6⟨2023⟩), in zirconium. На основі тензорної функції Гріна для гексагональних кристалів, одержаної методом Ліфшиця-Розенцвейга, пораховано аналітичний вираз енергії пружної взаємодії радіаційних точкових дефектів у моделі силових диполів з дислокаційною вакансійною петлею (базисна площина залягання {0001}, вектор Бюргерса bᴰˢ = 1/6⟨2023⟩) у цирконії. На основе тензорной функции Грина для гексагональных кристаллов, полученной методом Лифшица-Розенцвейга, посчитано аналитическое выражение энергии упругого взаимодействия радиационных точечных дефектов в модели силовых диполей с дислокационной вакансионной петлей (базисная плоскость залегания {0001}, вектор Бюргерса bᴰˢ = 1/6⟨2023⟩) в цирконии.